New primers for amplification of cytochrome c oxidase subunit I barcode region designed for species of Decapoda (Crustacea) - Mantelatto, Fernando L.; Carvalho, Fabricio L.; Simoes, Sabrina M. [UNESP]; Negri, Mariana; Souza-Carvalho, Edvanda A.; Terossi, Mariana (Soc Brasileira Carcinologia, 2016)
We designed 14 new primers for amplification of the COI barcode region of decapod crustacean species. We tested, with high level of success, the generation of similar to 640 +/- 49 base-pair sequences in selected groups of decapods (hermit crabs, squat lobsters, marine and freshwater crabs and shrimps), encompassing representatives of 27 genera of 15 families, 11 of Pleocyemata (Anomura, Brachyura, and Caridea) and 4 of Dendrobranchiata. Based on the results we expect the applicability of these primers for several studies with different taxa within Decapoda.
Keywords: COI; DNA Barcoding; molecular markers; molecular techniques